Entrepreneurship-Based Model of Pesantren Economic Empowerment at Pesantren NW Al-Rahman, West Lombok - Apip, Apipuddin; Siti Zaenab; Muslihun; Muhammad Yusup (JURNAL PENELITIAN KEISLAMAN, 2024)
This research centers on the asset management model for developing superior commodities within the plantation sector, specifically implemented by Pesantren NW Al-Rahman. The study employs a descriptive qualitative approach and a case study strategy to explore economic empowerment programs and activities at Pesantren NW Al-Rahman NW in West Lombok. Data collection methods include observation, interviews, and documentation. Subsequently, data analysis adheres to the Miles and Huberman model. The findings reveal that pesantren embrace entrepreneurship-based empowerment in the plantation sector by harnessing the potential of local commodities such as durian, palm sugar, kolang kaling, and oyster mushrooms. Pesantren NW Al-Rahman assumes three pivotal roles within this model: owner, distributor, and marketer. The implications extend beyond the school itself, impacting operational costs, enhancing soft skills for students, and increasing personal income for neighboring communities.